解方程9^x+6^x=2^2x+1是2^(2x+1)

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/16 14:06:49
解方程9^x+6^x=2^2x+1是2^(2x+1)

解方程9^x+6^x=2^2x+1是2^(2x+1)
解方程9^x+6^x=2^2x+1
是2^(2x+1)

解方程9^x+6^x=2^2x+1是2^(2x+1)
因为 9^x+6^x=2^2x+1
所以 3^2x + (2*3)^x = 2^2x + 1
即 (3^x - 2^x)(3^x + 2^x) = 1 - (2*3)^x
= 1 - (2^x)*(3^x)
当 x > 0 时 (3^x - 2^x)(3^x + 2^x) > 0
而 1 - (2^x)*(3^x) < 0
当 x < 0 时 (3^x - 2^x)(3^x + 2^x) < 0
而 1 - (2^x)*(3^x) > 0
只有 当 x = 0 时 (3^x - 2^x)(3^x + 2^x) = 0 = 1 - (2^x)*(3^x)
即 方程 的解为 x = 0

没看懂

9^x+6^x=2*4^x,两边除以6^x,(3/2)^x+1=2*(2/3)^,令(3/2)^x=u,则u+1=2/u,u^2+u-2=0,(u-1)(u+2)=0,于是u=1or-2(舍去),(3/2)^x=1,x=0.得啦.这题关键是注意到4,6,9这三个数的关系.